Effects of energy window width on planar image quality of thyroid imaging using single-headed gamma camera - Jamsari, Nur Liyana (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
The aim of this study is to evaluate the effects of energy window width on the planar image quality of thyroid phantom. The values of contrast and signal to noise ratio (SNR) were evaluated in this study. It was carried out by using a thyroid phantom that had been filled with 5.566 mCi Tc-99m radioactive sources. A static image of the thyroid phantom was captured using the single headed gamma camera (Symbia-E) at five different energy window widths of 10%, 15%, 20%, 30% and 40% which was equipped with LEHR collimator, stopping condition 300 kilocounts and matrix size of 128 x 128. The average counts obtained were recorded in a table and the contrast and SNR for hot and cold nodules were calculated using the given equation. For contrast, 15% energy window width gave the highest values for the hot nodules but for the cold nodules, it gave lower contrast values compared to 40%. However, the cold nodule at 15% energy window width gave the higher contrast values than 10%, 20% and 30% energy window widths. For SNR, the energy window width of 15% gave the highest values at all four nodules (two hot nodules and two cold nodules). Therefore, the optimum energy window width was the 15% for Tc-99m radioactive and planar imaging for thyroid.